Seizing Opportunities: The Moderating Role of Managerial Characteristics on the Relationship between Opportunity‐Seeking and Innovation Efficacy in Small Businesses. (1st October 2016) - Cooper, Danielle; Peake, Whitney; Watson, Warren
Abstract : We draw from regulatory focus theory to examine the relationship between a focus on opportunities through strategic orientation and entrepreneurial culture and managerial reports of innovation efficacy in small businesses. We propose that manager goals and behaviors moderate these relationships. Hypotheses were tested on a sample of 352 small employer firms. Findings support that strategic orientation positively associates with innovation efficacy and that this relationship is stronger under low managerial direction behaviors. Entrepreneurial culture positively associates with innovation efficacy when managers focus on profit and growth goals and under high managerial direction behaviors.